Possible superconductivity above 40 K in rhenium-doped strontium ruthenates indicated by Fourier-transform infrared spectroscopy - Yurii Aleshchenko; Boris Gorshunov; Elena Zhukova; Andrey Muratov; Alexander Dudka; Rajendra Dulal; Serafim Teknowijoyo; Sara Chahid; Vahan Nikoghosyan; Armen Gulian (Physical Review Research, 2020)
Strontium ruthenates have a lot of similarities with copper oxide superconductors and are a very interesting object for investigation of mechanisms and conditions which lead to high-temperature superconductivity. We report here on multiple experimental indications of superconductivity with the onset above 40K in strontium ruthenate doped by rhenium and selenium with chlorine used as a flux. The main experimental evidence comes from FTIR spectroscopy of this material followed by the ac and dc magnetization, as well as its heat capacity and magnetoresistance. Structural and morphological studies reveal the heterophase nature of this polycrystalline material as well as changes of lattice parameters relative to the original phases. Experimental data provide evidence of higher critical temperature on the surface compared to that in the bulk of the sample.